New evidence on an episode of geomagnetic instability, recorded in middle Miocene lava flows in Northwest Iceland - Kristjánsson, Leó (Studia Geophysica et Geodaetica)
Information on the character of paleomagnetic polarity transitions and major excursions is important to understanding of the generation of the geomagnetic field. The main aim of this study was to extend previous observations on a complex excursion event at around 13 Ma, recorded in lava flows south of the Ísafjarðardjúp fjord in the Northwest peninsula of Iceland. Core samples were collected in four short hillside profiles, for measurement of their remanence vectors after conventional alternating-field treatment. Despite minor hydrothermal alteration in the area, reliable estimates of primary geomagnetic directions were obtained in 49 of the 51 sites sampled. It is shown that large directional variations were taking place between at least 25 successive flows. Judging from the overall rate of buildup of the local lava pile, the duration of this event may reach 100 kyr. The results support findings in the literature on the occurrence of other episodes of geomagnetic instability in the Neogene. The excursion sequence in Ísafjarðardjúp will also be of value for stratigraphic correlation in the Northwest peninsula (and even farther afield), as it is probably contemporaneous with an excursion found 30 km away. Leó Kristjánsson. Obsahuje seznam literatury